Calculation of harmonic losses and ampacity in low-voltage power cables when used for feeding large LED lighting loads. - Milardovich, Natalio; Prevosto, Leandro; Lara, Marcela (My University, 2014)
A numerical investigation on the harmonic disturbances in low-voltage cables feeding large LED loads is reported. A frequency domain analysis on several commercially available LEDs was performed to investigate the signature of the harmonic current injected into the power system. Four-core cables and four single-core cable arrangements (three phases and neutral) of small, medium, and large conductor cross sections, with the neutral conductor cross section approximately equal to the half of the phase conductors, were examined. The cables were modelled by using electromagnetic finite-element analysis software. High harmonic power losses (up to 2.5 times the value corresponding to an undistorted current of the same rms value of the first harmonic of the LED current) were found. A generalized ampacity model was employed for re-rating the cables. It was found that the cross section of the neutral conductor plays an important role in the derating of the cable ampacity due to the presence of a high-level of triplen harmonics in the distorted current. The ampacity of the cables should be derated by about 40 %, almost independent of the conductor cross sections. The calculation have shown that an incoming widespread use of LED lamps in lighting could create significant additional harmonic losses in the supplying low-voltage lines, and thus more severe harmonic emission limits should be defined for LED lamps.
Keywords: Low-voltage.; Harmonic losses.; LED lamps.